Answer:
![n=-4.5m](https://tex.z-dn.net/?f=n%3D-4.5m)
Step-by-step explanation:
solve for n so that m becomes the independent variable
![-2m-5n=7m-3n](https://tex.z-dn.net/?f=-2m-5n%3D7m-3n)
![-5n=9m-3n](https://tex.z-dn.net/?f=-5n%3D9m-3n)
![-2n=9m](https://tex.z-dn.net/?f=-2n%3D9m)
![n=-4.5m](https://tex.z-dn.net/?f=n%3D-4.5m)
E ∩ F = {}
Step-by-step explanation:
Intersection is an operation performed on sets. In intersection, the common elements of the sets involved are written,
Given
E = {1, 2, 3}
F = {101, 102, 103, 104}
We have to find the intersection of both sets as indicated
So,
E ∩F = {1, 2, 3} ∩ {101, 102, 103, 104}
E ∩ F = {}
As there are no common elements in both sets the intersection will be an empty set
Keywords: sets, operations
Learn more about sets at:
#LearnwithBrianly
Missing part of question
(a) (-3, 4) and (5, 4)
(b) (4, 5) and (4, -3).
Answer:
(a) (-3, 4) and (5, 4)
Zero slope
Horizontal line
(b) (4, 5) and (4, -3).
Undefined slope
Vertical line
Step-by-step explanation:
Solving (a): (-3, 4) and (5, 4)
Slope (m) is calculated as:
![m = \frac{y_2 - y_1}{x_2 - x_1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_2%20-%20y_1%7D%7Bx_2%20-%20x_1%7D)
This gives
![m = \frac{4-4}{5 - -3}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B4-4%7D%7B5%20-%20-3%7D)
![m = \frac{0}{8}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B0%7D%7B8%7D)
![m = 0](https://tex.z-dn.net/?f=m%20%3D%200)
This line has a slope of zero.
When slope equals 0, then the line is horizontal
Solving (b): (4, 5) and (4, -3)
Slope (m) is calculated as:
![m = \frac{y_2 - y_1}{x_2 - x_1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_2%20-%20y_1%7D%7Bx_2%20-%20x_1%7D)
This gives
![m = \frac{5--3}{4-4}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B5--3%7D%7B4-4%7D)
![m = \frac{8}{0}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B8%7D%7B0%7D)
<em>m = undefined</em>
This line has an undefined slope.
When the slope of a line is undefined, then the line is vertical
550<600 it's something like that
(2,5)(-1,8)
slope = (8 - 5) / (-1 - 2) = 3/-3 = -1
y - y1 = m(x - x1)
slope(m) = -1
(2,5)...x1 = 2 and y1 = 5
now we sub
y - 5 = -1(x - 2) <==